Reducing cost drivers in total joint arthroplasty: understanding patient readmission risk and supply cost. Issue 2 (4th May 2018) - Swenson, Eric R.; Bastian, Nathaniel D.; Nembhard, Harriet B.; Davis III, Charles M.
ABSTRACT: Introduction: Understanding and planning for the factors that impact supply cost and unplanned readmission risk for total joint arthroplasty (TJA) patients is helpful for hospitals at financial risk under bundled payments. Readmission and operating room supply costs are two of the biggest expenses. Methods: Logistic and linear regressions are used to measure the impacts of TJA patient attributes on readmission risk and supply costs, respectively. Results: Patients' health market segment and the number/type of comorbidity impacts 30/90-day readmission rates. Surgeon implant preference and type of surgery impact supply costs. Discharge location and two of the five health market segments increase the odds of 30-day readmission. Arrhythmia and lymphoma are the primary comorbidities that impact the odds of readmission at 90 days. Conclusions: Preoperatively identifying TJA patients likely to have large supply costs and higher readmission risk allows hospitals to invest in low-cost interventions to reduce risk and improve healthcare value.